Exploring adaptive policy management and evaluation for improved water resources management in the face of uncertainty and complexity in South Africa - Ngcamphalala, Sandile (Department of Environmental and Geographical Science, 2022)
Evidence-based water resources policy management is bedevilled by the challenge of uncertainty, with increased risk of policy failure and/or unintended or negative policy outcomes. Moreover, there is increased policy management complexity emerging from related systems' interdependencies particularly between the water resources policy management system with other environmental, economic, social and political systems. Such complexity imposes external interference with the performance dynamics of water resources policy management efforts. Consequently, water resources policy management strategies in furtherance of ‘water equity' as the ultimate goal of water resources management policy in South Africa, may be misplaced. As a result, the performance of water resources management policy is unlikely to follow a linear logic of change/impact. The adoption of adaptive policy management strategies to ensure policy flexibility and efficiency is warranted especially for policies managed in the face of deep uncertainty and complexity mainly driven by the interactions and interdependencies between numerous social, economic, environmental and political variables with risk for the emergence of more unpredictable policy outcomes. Successful adaptive policy management, however, must be guided through real-time credible and comprehensive evidence, which is complicated to generate in a context plagued with deep uncertainty and complexity. Using systems mapping as a systems' analysis tool, this study identified a comprehensive list of environmental, economic, social and political variables that interactively determine water resources policy management performance towards ‘water equity'. The different environmental, economic, social and political variables that interactively influence ‘Water Equity' results as identified in this study, help to determine key policy drivers and leverage points that can be monitored and evaluated in pursuit of credible and comprehensive water resources policy planning, implementing and performance evidence. The availability of credible and comprehensive evidence, however, does not imply automatic success of the adopted adaptive strategy. The study found that there are numerous other barriers on different aspects and levels of the policy that would have to be addressed to ensure the contextual success of adaptive and integrated water resources policy management in South Africa. These include, transformational changes in substantive water resources management policy design to ensure proactive intentionality to improve water resources policy management in the face of deep uncertainty; designing institutional policy governance structures that demonstrate clear appreciation of the heterogeneous water resources management needs across the country; and active commitment to fully and timely implementation policy decisions in a manner that ensures continuous learning, capitalises on policy performance opportunities, defends working policy strategies and facilitates real-time policy corrections.